PROFESSOR ÓSERBAY ÁLEWOVTÍŃ MIYNETLERINDE TÁLIM-TÁRBIYA MÁSELELERI - Kosbergenov, B.M. (ILIM hám JÁMIYET, 2023)
Professor U.Aleuov's scientific articles talk about the pedagogy of folklore, traditions, the role of folk folklore in youth education.